Association Between Visfatin Levels and Coronary Artery Disease in Patients with Chronic Kidney Disease (Iranian Journal of Kidney Diseases, 2013)
Introduction. Visfatin (also known as pre-B cell colony-enhancing factor) is increased in patients with chronic kidney disease and has been linked with coronary atherosclerosis. Given that it has been reported that visfatin plays a role in endothelial dysfunction in chronic kidney disease patients, we examined associations between visfatin levels and several markers related to atherosclerosis. Materials and Methods. The association between visfatin and atherosclerotic risk factors was studied in 173 chronic kidney disease patients (130 men and 43 women). Serum levels of visfatin were measured by the enzyme-linked immunosorbent assay. Results. With increasing visfatin tertiles, patients proved to have a larger number of vessels with stenosis and a higher likelihood of coronary artery disease, as well as having incrementally lower estimated glomerular filtration rate and serum albumin and higher total leukocyte, neutrophil, and monocyte counts; high-sensitivity C-reactive protein; and brain natriuretic peptide levels. Visfatin showed significant positive correlations with low-density lipoprotein cholesterol, uric acid, blood urea nitrogen, creatinine, brain natriuretic peptide, E-selectin, total leukocyte count, neutrophil count, and high-sensitivity C-reactive protein, and a significant negative correlation with estimated glomerular filtration rate and albumin. Only E-selectin was independently associated with visfatin in multiple linear regression analysis. Conclusions. This study indicates that plasma visfatin levels are significantly higher in the presence of coronary artery disease and are correlated with E-selectin levels, which suggest that increased plasma visfatin may be involved in the pathogenesis of coronary atherosclerosis in CKD patients.